UKRAINIAN POST-WAR MIRACLE: FROM PLAN TO IMPLEMENTATION - OPANASIUK, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the study of the experience of post-war reconstruction of Germany, South Korea, Israel, Spain, Italy, Japan in order to analytically select the most convenient tools for post-war reconstruction of Ukraine. Relevance of the problem. This is a great chance to turn to the development strategy of Ukraine. In addition, the relevance of this article is based on the idea that security, security strategy, and then other issues of state building and development should be primary. The economic sector must answer the question: what strategy of rebuilding Ukraine meets the national economic security interests? What is more important for Ukraine: restoration, reconstruction or reconstruction? What subjective new role should Ukraine begin to develop: niche, blockless, boutique economy or world deep specialization and integration? What competitive advantages should Ukraine increase and what gaps should be closed independently or in cooperation with the world? Mankind, unfortunately, has accumulated some experience of post-war development. Some countries, like North Korea, have done this very effectively, but not quickly and not on the first attempt. Some, like Germany, have discovered the "German economic postwar miracle" to the world, although it has lost for a time subjectivity in many areas in favor of the United States. Some countries, such as Israel and Japan, have also created an "economic miracle", each country in its own way, but with unconditional help from the United States. The task for searching is to study and select the best experience and tools for restoring the state of Ukraine based on the experience of different countries that have passed this path. Research methods. The methodological and informational basis of the work are scientific works, materials of periodicals, Internet resources, normative legal acts. Own survey among 100 people of different professions, aged from 20 to 70 and balanced gender representation. The novelty lies in the very relevance of the study: after all, only martial law requires doing research and looking for a solution for the postwar period. The conclusions presented by this study cannot be over-innovative, but must be conservative, balanced and justified. Practical significance 10 deterministic conclusions-proposals that can be used by Ukraine in the post-war period are proposed.